Organic Fertilizer Application Mediates Tomato Defense Against Pseudomonas syringae pv. Tomato, Possibly by Reshaping the Soil Microbiome - Huang, Feng; Mo, Chunhao; Li, Linfei; Shi, Jingling; Yang, Yiwen; Liao, Xindi (Frontiers in Microbiology, 2022)
Bacterial speck caused by Pseudomonas syringae pv. tomato is a serious foliar disease on tomato. However, it is still unknown how organic fertilizers application mediates plant defense against foliar pathogens by altering the composition of the soil microbial community. We conducted a 2-cycle pot experiment involving chemical and organic fertilizers and tracked tomato foliar pathogen incidence. Using microbiome sequencing, we then compared the differences in bulk and rhizosphere microbial communities. The results showed that, compared with soils amended with chemical fertilizer, soils amended with organic fertilizer gradually and significantly presented a reduction in tomato foliar disease, and the bacterial richness and diversity significantly increased. Moreover, the bacterial and fungal compositions of the bulk soil and rhizosphere soil of the organic fertilizer and chemical fertilizer treatments were different from each other. More importantly, the abundance of some potentially beneficial bacteria, such as Luteolibacter, Glycomyces, Flavobacterium, and Flavihumibacter, increased in the organic fertilizer-amended soil, and these genera were significantly negatively correlated with the incidence of tomato foliar disease. These results suggest that organic fertilizers can alter the taxonomy of the soil microbiome and that some specific beneficial microbial communities may play an important role in reducing the infection of foliar pathogens by inducing plant resistance.